Analisis Kualitas Air Pasca Tambang Emas d i Desa Wumbubangka , Kec a matan Rarowatu , Kabupaten Bombana - Gani, Abdul; Rosdiana, Rosdiana; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
Southeast Sulawesi Province has great mining potential to support Indonesia's national mining. Especially in Bombana Regency, it has the potential for gold mining, but with mining activities, the mining area becomes nutrient-poor and toxic. Based on this research, we observed the levels of pH, mercury (Hg), Total Suspended Solid (TSS), Copper (Cu) that accumulated in the waters around the gold mining area. The results showed that the pH level in sector 1 was 9.5 and sector 2 was 9.72. The Hg level also shows -0.0021 mg/L and -0.0014 mg/L. On the other hand, the high TSS content for sector 1 was 930 mg/L due to the sampling point being very close to the gold mining sector, while sector 2 started to decline by 410 mg/L. Cu analysis showed the same value, namely -0.00032 mg/L, it was concluded that the gold quality in sectors 1 and 2 had the same grade.